DIVERSITÉ FLORISTIQUE DU MASSIF DU NADOR EN ZONE STEPPIQUE (TIARET, ALGÉRIE) - Benkhettou, Abdelkader; Azouzi, Blel; Djili, Kadour; Mohamed, Benkhettou; Zedek, Mohamed; Saadi, Rachid (European Scientific Journal, ESJ, 2015)
This study is devoted to Nador massif located in the steppe environment of Tiaret region in the west of Algeria. This massif is characterized by a diversity of flora composed of 121 taxa belonging to 38 families and 98 genera. Biological spectrum indicates a predominance of therophytes (38%) and chamaephytes (19%), geophytes (14%). The most important families are Poaceae and Asteraceae. Mediterranean element is relatively dominant (55%) according to chorologic plane. Shannon-Weaver e diversity index is relatively high (4.55) indicating a richly diverse site. Disturbance index (63.6%) reflects highly significant degree of massif vegetation disturbance, which also reflects a more open environment. To better understand the structure of vegetation using the classification is imperative